Pengaruh Job Knowledge dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan - Yosefonsus Tono; Didik Subiyanto; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine: 1) the effect of job knowledge on job satisfaction of sanggar jumputan maharani employees , 2) the influence of motivation on job satisfaction of employees of sanggar jumputan maharani and 3) the influence of job knowledge and motivation on job satisfaction of sanggar jumputan maharani employees.The population of this study was 30 permanent employees of the sanggar jumputan maharani yogyakarta. The number of Samples used was 30 respondents of permanent employees of the sanggar jumputan maharani celeban yogyakarta. The sampling technique used is the probability sampling technique. The data collection techniques used are questionnaires and interviews. The data was analyzed by using IBM SPSS Version 25 applications. The results of this study show that the variability of job knowledge (X1) has a positive and significant effect on employee job satisfaction (Y) with a value of 5,722. Then the variable motivation (X2) has a positive and significant effect on employee job satisfaction (Y) with a value of 6,146. The variables Job knowledge (X1) and motivation (X2) have a positive and significant effect on employee job satisfaction (Y) with a value of 0.624. So it can be concluded that all variables in this study have a positive influence on employee job satisfaction. Keywords: Job knowledge, Motivation, Employee job satisfaction.